2011
DOI: 10.1111/j.2041-210x.2010.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

The demography of space occupancy: measuring plant colonization and survival probabilities using repeated pin‐point measurements

Abstract: Summary1. The study of plant demography has long been an important component of plant ecological studies. However, in plant communities, e.g. grasslands, where individual plants are not easily distinguished and often vary in size, a convenient method of describing the demography and its ecological consequences has been lacking. 2. The aim of this study was to discuss the potential for using the change in the probability of space occupancy as a measure of ecological success in plant population biology. This wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…The point intercept method provides information about three dimensional vegetation structure (Godínez-Alvarez et al 2009, Jonasson, 1988, and repeated point intercept method is also suitable for plant demography studies due to its precise positioning within the sampling unit (Damgaard et al 2011). However, we found that the method is not superior over other methods in the accuracy of biomass estimation.…”
Section: Discussioncontrasting
confidence: 43%
“…The point intercept method provides information about three dimensional vegetation structure (Godínez-Alvarez et al 2009, Jonasson, 1988, and repeated point intercept method is also suitable for plant demography studies due to its precise positioning within the sampling unit (Damgaard et al 2011). However, we found that the method is not superior over other methods in the accuracy of biomass estimation.…”
Section: Discussioncontrasting
confidence: 43%
“…The quantitative effect of survival and colonization processes on population growth of individuals is most effectively summarized using population models [28], and the calculation of elasticity (the relative contribution of different demographic parameters on population growth rates) has particularly been shown to be a powerful tool to investigate the importance of different demographic variables in determining population growth [18].…”
Section: Methodsmentioning
confidence: 99%
“…grasslands, it is often difficult to distinguish individual plants due to their vegetative growth pattern and, consequently, to obtain reliable demographic data. Instead, it is possible to measure “colonization” and “survival” by considering the turnover of a species at a specific spatial point [18]. Considering such a specific spatial point, then if the species was present at time t but absent at time t +1, we may loosely speak of a mortality event, and if the species is absent from a specific pin-position at time t and present at time t +1, we may loosely speak of a colonization event [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ground covered by the sown species relative to weeds and uncovered bare soil was assessed by the pin point method, which measures the proportion of ground occupied by a perpendicular projection on to it of the aerial parts of the plants (Damgaard et al, 2011). A frame with a fixed grid pattern was placed randomly…”
Section: Field Data Recovery and Laboratory Analysismentioning
confidence: 99%